The Environmental Kuznets Curve: Exploring a Fresh Specification - David Bradford; Rebecca Schlieckert; Stephen H. Shore (Center for Economic Studies and ifo Institute (CESifo), 2000)
Using a new specification, we reanalyze the data on worldwide environmental quality investigated by Gene Grossman and Alan Krueger in a well-known paper on the environmental Kuznets curve (which postulates an inverse U shaped relationship between income level and pollution). The new specification enables us to draw conclusions from fixed effects estimation. In general, we find support for the environmental Kuznets curve for some pollutants and for its rejection in other cases. The fresh specification offers some promise for analysis of such phenomena.
Keywords: 330